Pengaruh Masa Kerja, Kedisiplinan, Motivasi Dan Prestasi Kerja Terhadap Jenjang Karir Karyawan Pada PT Great Giant Pineapple Lampung Tengah - Lestari, Retno Dina; Dupri, Muhammad Demsi (Universitas Muhammadiyah Metro, 2022)
Retno Dina Lestari. 2021. “The Influence of Working Period, Discipline, Motivation and Work Achievement on Career Paths of Employees of PT. Great Giant Pineapple Central Lampung”. Thesis Management Study Program, Faculty of Economics and Business. University of Muhammadiyah Metro. Supervisor (1) H. Suryadi S.E., M.M. Supervisor (2) H. Suwarto S.E,. M.M. This research was conducted at PT. Great Giant Pineapple Central Lampung is engaged in pineapple plantations. Where its operational activities require competent workers, therefore human resource management must be improved. This study aims to determine the effect of tenure, discipline, motivation and work performance on the career paths of employees at PT Great Giant Pineapple Central Lampung in 2020. about distributing questionnaires in the form of tenure, discipline, motivation and work on employee career paths. Then processed with SPSS version 21 with the classical assumption test approach with the methods of normality, linearity, homogeneity. This study uses quantitative methods with multiple regression analysis, partial test, F test, determination to determine the effect of tenure, discipline, motivation and work performance on the career path of Great Giant Pineapple employees. The results of the study indicate that simultaneously the tenure, discipline, motivation and work performance of employees' career paths. Partial research shows that tenure has a positive and significant effect, discipline has a positive and significant effect, motivation has a positive and significant effect, and work performance has a positive and significant effect on employee career paths. Keywords: Working Period, Discipline, Motivation, Work Achievement, Career Path